International Cooperation in Science and Technology: Concepts, Contemporary Issues and Impacts on BrazilAs Future (Global Journal of Management and Business Research, 2014)
This article discusses international cooperation in science and technology (S&T), analyzing crucial contemporary issues, as well as Brazilian-specific issues, based on the literature of the area and concrete examples of the field. It presents concepts, main terminologies and typologies, with contributions from specialists in different periods for the theme. Furthermore, it introduces a reflection on technique and human nature, exploring the vectors of the scientifictechnological cooperation and the technical cooperation. The paper also provides a short historical overview of international cooperation, notably in the periods separated by the Cold War. Through recent instances, it outlines key issues of international cooperation in S&T and the reality of Brazil with respect to the powerful tool of foreign governmental policy.
Keywords: science; technology; cooperation; foreign policy